Dairy sheep nutrition - Pulina, Giuseppe; Bencini, Roberta (Cabi Ser., 2004)
"This book is a translation of a popular Italian text, originally published in 2001, and includes some revisions and updates. It contains chapters on all aspects of dairy sheep nutrition and feeding, such as milk production, feed intake, nutrition and reproduction, nutrition and milk quality, and grazing and stocking rate management. The book will appeal to researchers in sheep nutrition, vets and producers."--Jacket